Circulating Exosomal MiR-107 Restrains Tumorigenesis in Diffuse Large B-Cell Lymphoma by Targeting 14-3-3η - Liu, Jiarui; Han, Yang; Hu, Shunfeng; Cai, Yiqing; Yang, Juan; Ren, Shuai; Zhao, Yi; Lu, Tiange; Zhou, Xiangxiang; Wang, Xin (Frontiers in Cell and Developmental Biology, 2021)
Exosomes, nanometer-sized membranous vesicles in body fluids, have emerged as promising non-invasive biomarkers for cancer diagnosis. However, the function of exosomes in diffuse large B-cell lymphoma (DLBCL) remains elusive. This study aimed to investigate the role of exosomal miR-107 in lymphomagenesis and explore its clinical significance. In this study, decreased exosomal miR-107, miR-375-3p, and upregulated exosomal miR-485-3p were detected in the plasma of DLBCL patients and showed potential diagnostic value. Downregulated miR-107 expression was associated with advanced Ann Arbor stage, high IPI score, LDH, and β2-MG level in DLBCL patients. Overexpression of miR-107 by miR-107 Agomir significantly abrogated cell proliferation, induced apoptosis, and inhibited cell invasion in vitro, and repressed tumor growth in vivo. Moreover, the downregulation of miR-107 went in the opposite direction. The target genes of miR-107 were mainly enriched in the PI3K-Akt, Hippo, and AMPK signaling pathways. Notably, upregulated 14-3-3η (YWHAH) was suppressed by miR-107 in DLBCL, suggesting that miR-107 may restrain tumorigenesis by targeting 14-3-3η. In summary, this study unveils the function of miR-107 in lymphomagenesis, highlighting its potential as a diagnostic and prognostic indicator and as a new therapeutic target in the management of DLBCL.